Nationalism and social policy. The politics of territorial solidarity - Beland, Daniel; Lecours, André (New York, 2008)
"Despite the recent proliferation of literature on nationalism and on social policy, relatively little has been written to analyze the possible interaction between the two. Scholars interested in social citizenship have indirectly dealt with the interaction between national identity and social programs, but they have seldom examined this connection in reference to nationalism. Specialists of nationalism rarely mention social policy, focusing instead on language, culture, ethnicity, and religion. The main objective of this book is to explore the nature of the connection between nationalism and social policy from a comparative and historical perspective. At the theoretical level, this analysis will shed new light on a more general issue: the relationships between identity formation, territorial politics, and social policy.